The Legal Proportion of Bequests in Hadith And Islamic Economics: Implications For Family and Social Welfare - Nasrun, Mahdalena (Prodi Ilmu Hadis Fakultas Ushuluddin dan Filsafat UIN Ar-Raniry Banda Aceh, 2025)
A bequest (waṣiyyah) is a noble act and a source of blessings in Islam, regarded as one of the enduring good deeds (ṣadaqah jāriyah). However, complications may arise when a bequest is made in favor of legal heirs, who already have designated shares in inheritance, including cases where the sole heir is a daughter. Such situations become contentious due to another hadith prohibiting bequests to legal heirs. This raises the question: What is the permissible extent of a bequest when the sole heir is a daughter? How should the hadith forbidding bequests to heirs be interpreted through the lens of Islamic economic jurisprudence, and what are its implications for family and community economics? This study employs a qualitative methodology using both fiqh al-ḥadīth and Islamic economic approaches. The findings reveal that a bequest is considered excessive if it exceeds one-third of the estate. The primary hadith governing this ruling is ṣaḥīḥ and included in the authoritative Kutub al-Tis‘ah. Conversely, the hadith prohibiting bequests to heirs without their consent is graded as ḥasan li-ghayrih and lacks the criteria for ṣaḥīḥ classification according to Imam al-Bukhārī, although it is transmitted through multiple chains. In cases where the sole heir is a daughter, she receives her prescribed share and may also benefit from the residual portion (ʿaṣabah) within the permissible one-third bequest. This ruling reflects the Prophetic vision to uphold justice in economic distribution and protection of vulnerable groups, such as daughters, aligning with the objectives of the Sharīʿah (maqāṣid al-sharīʿah), particularly the preservation of wealth (ḥifẓ al-māl) and lineage (ḥifẓ al-nasl). Islamic economics is founded not on socialism or capitalism, but on five core values: tawḥīd (monotheism), nubuwwah (prophethood), khilāfah (vicegerency), ʿadl (justice), and maʿād (accountability in the hereafter). Within this framework, the prohibition of bequests to heirs can be reinterpreted as an opportunity to strengthen economic stability in families and society, especially in special cases such as children with disabilities, adopted children, foster parents, and others.